PEMAHAMAN ORANG TUA TENTANG KONSEP PAUD DI TK AL-KHOLIDIYAH SEDINGINAN KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Sari, Nopita; Chairilsyah, Daviq; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to determine "the parents understanding of the concept of early childhood education at TK Al-Kholidiyah Sedinginan Tanah Putih Rokan Hilir". Results of this study are expected to be useful as knowledge and as a discourse of knowledge and learning in knowing about the analysis of the parents understanding of the concept of early childhood education at TK Al-Kholidiyah Sedinginan Tanah Putih Rokan Hilir. The population in this study are all the parents that the student's mother in TK Al-Kholidiyah Sedinginan Tanah Putih by 84 mothers of students. The sample used in this study were 46 respondents in TK Al-Kholidiyah Sedinginan Tanah Putih. The data collection techniques that scale in Likert Scale. Data were analyzed using trial scale and statistical methods using SPSS for Window Ver.16.0 The results of data can be seen from the percentage of the overall indicator results the parents understanding of the concept of early childhood education at TK Al-Kholidiyah Sedinginan Tanah Putih Rokan Hilir with a percentage 74.18% and classified in the category of "good". The conclusion of this study parental understanding of the concept of early childhood education at TK Al-Kholidiyah Sedinginan Tanah Putih Rokan Hilir classified in both categories with pesentase 74.18%Keywords: understanding, parents, pre-school, early childhood